2010
DOI: 10.1002/etc.107
|View full text |Cite
|
Sign up to set email alerts
|

Leaching potential of nonsteroidal anti‐inflammatory drugs in soils

Abstract: Abstract-Nonsteroidal anti-inflammatory drugs (NSAIDs) in soils resulting from application of municipal wastewater or biosolids may migrate through soils intact or be transformed and reach groundwater. In the present study, the leaching potential of four NSAIDs (ibuprofen, naproxen, ketoprofen, and diclofenac sodium) in three U.S. cropland soils was evaluated, and the effect of CaCl 2 solution (as an index of salinity), dissolved organic matter (DOM), and polyacrylamide (PAM) amendment was investigated. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Although the Langmuir model does not completely explain the phenomenon, it was observed that the soil with the highest value of maximum adsorption, 76.6, corresponded to soil B, which was also the soil with the highest value of organic matter content, 3.51%, whereas soil C, with the lowest value of maximum adsorption, 38.2, was the soil with the lowest clay content, 15.0%. These results are to be expected because both organic matter and clay content are usually directly related to adsorption of contaminants in soils (Xu et al 2010), although other studies have reported that clay content does not play a major role (Lin and Gan 2011). It can be seen from the Freundlich adsorption parameters that adsorption was low, as indicated by the Freundlich constant, K Fads , with values between 1.05 and 2.26, similar to reported data for adsorption of ibuprofen on sediments (Styszko et al 2010).…”
Section: Resultsmentioning
confidence: 73%
“…Although the Langmuir model does not completely explain the phenomenon, it was observed that the soil with the highest value of maximum adsorption, 76.6, corresponded to soil B, which was also the soil with the highest value of organic matter content, 3.51%, whereas soil C, with the lowest value of maximum adsorption, 38.2, was the soil with the lowest clay content, 15.0%. These results are to be expected because both organic matter and clay content are usually directly related to adsorption of contaminants in soils (Xu et al 2010), although other studies have reported that clay content does not play a major role (Lin and Gan 2011). It can be seen from the Freundlich adsorption parameters that adsorption was low, as indicated by the Freundlich constant, K Fads , with values between 1.05 and 2.26, similar to reported data for adsorption of ibuprofen on sediments (Styszko et al 2010).…”
Section: Resultsmentioning
confidence: 73%
“…The soil used in this study was characterized by a low content of organic matter and a high content of the sand fraction, which might result in a lower adsorption of NSAIDs to soil components and a higher availability of drugs for soil microorganisms (Xu et al, 2010; González-Naranjo et al, 2013; Vasiliadou et al, 2013; Estevez et al, 2014; Graouer-Bacart et al, 2016). This effect was also observed in relation to other organic compounds such as pesticides (Karpouzas and Walker, 2000; Liang et al, 2011; Cycoń et al, 2014), polycyclic aromatic hydrocarbons (Sverdrup et al, 2002; Rivas et al, 2008; Chen and Yuan, 2011) and other pharmaceuticals (Topp et al, 2008b; Sabourin et al, 2009; Al-Rajab et al, 2015; Barra Caracciolo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the water solubility and mobility of pharmaceutical compounds and soil properties, NSAIDs may be adsorbed to soil particles, leached into ground water or runoff into surface water. It has been reported that the leaching of IBF, DCF, NPX, and KTF is significant and is related to their pK a values as well as to the amount of clay and dissolved organic carbon (Xu et al, 2010; Estevez et al, 2014). Studies by Chefetz et al (2008) proved that both the content and physicochemical nature of soil organic matter (SOM) strongly influenced the sorption of DCF and NPX in SOM-rich soil layers.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviors of PPCPs in aquatic ecosystems are alarming (Onesios et al, 2009). The environmental fate and transport of the compounds in receiving soils need to be delineated (Xu et al, 2009b(Xu et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%